Advancement of regulating cellular signaling pathways in NSCLC target therapy via nanodrug - Li, Wenqiang; Li, Mei; Huang, Qian; He, Xiaoyu; Shen, Chen; Hou, Xiaoming; Xue, Fulai; Deng, Zhiping; Luo, Yao (Frontiers in Chemistry, 2023)
Lung cancer (LC) is one of the leading causes of high cancer-associated mortality worldwide. Non-small cell lung cancer (NSCLC) is the most common type of LC. The mechanisms of NSCLC evolution involve the alterations of multiple complex signaling pathways. Even with advances in biological understanding, early diagnosis, therapy, and mechanisms of drug resistance, many dilemmas still need to face in NSCLC treatments. However, many efforts have been made to explore the pathological changes of tumor cells based on specific molecular signals for drug therapy and targeted delivery. Nano-delivery has great potential in the diagnosis and treatment of tumors. In recent years, many studies have focused on different combinations of drugs and nanoparticles (NPs) to constitute nano-based drug delivery systems (NDDS), which deliver drugs regulating specific molecular signaling pathways in tumor cells, and most of them have positive implications. This review summarized the recent advances of therapeutic targets discovered in signaling pathways in NSCLC as well as the related NDDS, and presented the future prospects and challenges.